(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines the hygienic aspects of improving physical condition through health-enhancing physical culture and the development of physical fitness and wellness programs. The main principles of effectively using physical activity to improve health are identified, including the dosage of exercise based on age, physiological, and individual characteristics. Particular attention is paid to disease prevention through regular physical fitness and wellness activities, as well as the creation of individualized exercise programs for different social groups. The role of hygienic standards in developing effective physical wellness programs, which ensure safety and maximize results in improving physical condition, is analyzed. The importance of integrating physical activity and a healthy lifestyle as an integral part of disease prevention and overall health improvement is emphasized. To determine the purpose, objectives, content, and methodology of the study, classical literature on physical health and its dependence on physical activity, physical development, fitness levels, and influencing factors was analyzed. Hygienic aspects of improving physical condition through health-enhancing physical culture were studied, and effective approaches to programming physical fitness and wellness activities were developed, taking into account individual and age-specific characteristics that contribute to enhancing physical development and strengthening health. The article also addresses the assessment and correction of the physical condition of student youth, as well as the dependence of these indicators on the quality of physical education organization in higher education institutions. We developed physical fitness and wellness programs for students, considering their physical condition, age, and fitness level. The primary goal of this program is to improve key indicators of physical condition, including heart rate, blood pressure, body weight, strength, speed, speed-strength abilities, and overall endurance. These programs aim to achieve and maintain a high level of physical fitness and stable health over an extended period.